Changes in muscle measures during chemoradiotherapy in patients with limited stage small cell lung cancer. Issue 1 (15th September 2020) - Valan, Christine Damgaard; Halvorsen, Tarje Onsøien; Slaaen, Marit; Grønberg, Bjørn Henning
Abstract: Background: Concurrent chemoradiotherapy is the recommended treatment for limited stage small cell lung cancer. Severe side‐effects, which might cause loss of muscle mass, are frequent. Low skeletal muscle index (SMI) and radiodensity (SMD) are associated with inferior survival and more toxicity in cancer patients, but few have investigated this in small cell lung cancer, and none have investigated whether these muscle measures change during chemoradiotherapy. Patients from a trial comparing two schedules of thoracic radiotherapy (TRT) were analysed ( n = 157). We investigated if SMI and SMD changed during treatment; whether changes are negative prognostic factors; or associated with severe toxicity. Methods: Skeletal muscle index and SMD were assessed from computerized tomography scans taken before and after chemoradiotherapy. Patients with analysable computerized tomography scans who completed TRT were eligible. Results: Sixty‐eight patients (43.3%) were analysed. Median age was 63 (range 40–85), 16% had performance status 2 and 92% stage III. Mean SMI decreased from 46.25 to 42.13 cm 2 /m 2 and mean SMD from 38.40 to 37.46 Hounsfield units. Loss of SMD was significantly associated with less Grades 3–4 toxicity ( P = 0.027) and less Grades 3–4 esophagitis ( P = 0.029). Loss of SMI was significantly associated with shorter survival in multivariable ( P = 0.037) but not in univariable analysis ( P = 0.094). Loss of SMD was significantly associated with better survival in both univariable ( P = 0.006) and multivariable analyses ( P = 0.013). Conclusions: There were large individual variations in changes in muscle measures during chemoradiotherapy, but the majority experienced a loss of both SMI and SMD. There was no consistent prognostic value of changes in muscle measures or consistent associations with severe treatment toxicity.